Efforts to Improve the Performance of Class VI Teachers through Individual Supervision at SD Sukaharja I Karawang District - Kona'ah Kona'ah (Universitas Muhammadiyah Enrekang, 2023)
This research aims to improve the performance of Class VI teachers at SDN Sukaharja I, Karawang Tengah Regency in 2021/2022. This research will use Action Research, which is a type of research where people do something (in this case teacher guidance) and then study the results. Based on the results of the action research there was an increase in the performance of Class VI teachers from the beginning before the action was 58.3%, after the action in Cycle I it became 72.2%, and after the action in Cycle II it increased again to 94%. As for the learning outcomes of students there was a sharp increase from the initial conditions to learning outcomes after the action in cycle I, and there was also an increase after the action in cycle II, although the increase was not too sharp. The results of individual supervision action research on Class VI teachers are proven to provide an increase in the performance of Class VI teachers which in turn has an impact on improving student learning outcomes. Individual supervision can improve the performance of Class VI teachers in the lesson planning and learning implementation components. The increase in the performance of Class VI teachers has an impact on improving the learning outcomes of other subjects.